1986
DOI: 10.1007/bf00614309
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent pharmacokinetics of dexamethasone

Abstract: The dose dependency of the pharmacokinetics of dexamethasone and its influence on the endogenous secretion of cortisol has been studied in healthy females. The maximum plasma level occurred between 1.6 and 2.0 h after doses of 0.5-3.0 mg independent of the type of administration. AUC, distribution volume, plasma clearance and cmax did not increase in proportion to the dose but only by the factor of about 0.6-0.7 after the oral administration of 0.5-1.5 mg. Comparatively high values were reached after 3.0 mg i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
2
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 14 publications
5
41
2
1
Order By: Relevance
“…chronic (more than I year in Cushing's syndrome), 48, 12 and 3 h. The pharmacokinetic profile of Dex [21). as well as the cortisol values at 0 min, veri fied the dose-related effectiveness of the models.…”
Section: Discussionmentioning
confidence: 77%
“…chronic (more than I year in Cushing's syndrome), 48, 12 and 3 h. The pharmacokinetic profile of Dex [21). as well as the cortisol values at 0 min, veri fied the dose-related effectiveness of the models.…”
Section: Discussionmentioning
confidence: 77%
“…A study on liver transplant recipients who had received 1 g of methylprednisolonehemisuccinate by a 1-h intravenous infusion for the treatment of acute rejection demonstrated that maximum serum concentrations of methylprednisolone were from 16 to 46 mol/L, which correspond to the equivalent dexamethasone concentrations from 3.2 to 9.2 M (46). A pharmacokinetic analysis using RIA showed that the peak plasma concentration of dexamethasone was 0.0882 Ïź 0.0153 M after intramuscular injection of 3.0 mg of dexamethasone (47). On the basis of these data, we tested the effect of dexamethasone at the concentrations from Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Our intention was to have two models of corti coid administration whose main difference would be the time of hypothalamo-pituitary exposure to dexamethasone. In fact, pharmacokinetic studies on dexamethasone [9], as well as our own results (cortisol values a 0 time), show that both doses are biologically effective although the 8-mg dose was more powerful.…”
Section: Discussionmentioning
confidence: 99%